COMPARISON OF GOOD CORPORATE GOVERNANCE IMPLEMENTATION ON THE PERFORMANCE OF ISLAMIC COMMERCIAL BANKS (Comparative Study Tarakan Indonesia and Sabah Malaysia) - Ana Sriekaningsih (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2022)
The research was carried out to find out how far the strategy formulation, organizational commitment and leadership style affected to the implementation Good Corporate Governance that would influence the performance of Islamic Commercial Banks (ICB) in Indonesia and Malaysia. There were two research objects namely 53 employees of Islamic Commercial Banks in Indonesia and 53 employees in Malaysia. Data collection was done by using questionnaire, then validity and reliability test was done which has approved that data was valid and reliable. The data was analyzed by path analysis and processed by SPSS. The result of research showed that both countries’ governance was regulated in separated law and regulation with conventional system. Variable of strategy formulation and leadership style were significantly influenced to the implementation of good corporate governance on Islamic Commercial Banks in Indonesia and Malaysia. While the variable of organizational commitment was not significantly affected to the good corporate governance in Indonesia, but it had significant effect in Malaysia. Strategy formulation and organizational commitment had significant effect on the performance of Islamic Commercial Banks in Indonesia but leadership style had no significant effect on the performance. When the strategy formulation, organizational commitment, leadership style and good corporate governance implementation were regressed together to predict performance, strategy formulation and organizational commitment remain significant. However, leadership style and Good Corporate Governance implementation had no significant effect on the performance.